A Novel Expandable Catheter Wireless Amplified NMR Detector for MR Sensitivity Accessing the Kidney in Rodent Model - Timilsina, Roshan (IEEE Trans Biomed Circuits Syst, 2019)
This article demonstrates the enlarged effective range for MRI sensitivity enhancement with a deformable catheter MRI coils integrated with a wirelessly powered amplifier. The expandable balloon Wireless Amplified Nuclear magnetic resonance Detector (WAND) is constructed on a copper-clad polyimide film to resonate at the first and second harmonics of the proton Larmor frequency at 7 Tesla. The WAND is then mounted on a balloon catheter system for easy delivery inside confined orifice. Upon reaching the region of interest, it is unfolded out of the sheath tube to increase its effective size. Magnetic Resonance (MR) imaging experiments with and without the WAND are performed both in a water phantom and in a live rat to evaluate the WAND’s sensitivity advantage. Expanded from a 3 mm diameter in its folded state, this deformable WAND can change its width by > 100% in its inflated state to at least 6 mm, leading to a sensitive detection region extending to up to 20 mm in the transverse direction. When the deformable WAND is placed in an artery in the region of the kidney of a live rat, it could achieve at least a 10-fold SNR gain over images acquired by a standard external detector of 22 mm diameter, even though the region of interest is separated from the WAND’s surface by a distance larger than the WAND’s own width. The proposed expandable catheter WAND could significantly enlarge the effective range for MR sensitivity enhancement in-vivo, enabling versatile applications in interventional MRI.